Onkogenesis, Morfologi, dan Modalitas Deteksi Dini Karsinoma Serviks - Rapar, Elsani P. L.; Sambuaga, Maria K.; Durry, Meilany F. (Universitas Sam Ratulangi, 2021)
Abstract: The incidence and mortality rates of cervical cancer in developing countries are relatively high compared to developed countries. The main risk factor for cervical cancer is high risk human papilloma virus (HPV) infection, such as types 16 and 18. Types of high-risk HPV expresses oncoproteins E6 and E7 which play an essential role in the pathogenesis of cervical carcinoma through inhibition of the activity of gene group expression products that play a role in suppressing tumor growth, such as p53 and pRB. This process will cause morphological changes in the squamous epithelium from precancerous lesions to cancer. The development of squamous epithelial cell cancer can be prevented through screening tests in order to detect cervical cancer early. This study was aimed to obtain the oncogenesis, morphology, and early detection modality of cervical carcinoma. This was a literature review study using three databases, as follows: ClinicalKey, PubMed, and Google Scholar. The results explained that p53 and pRB suppression by high-risk HPV oncoproteins E6 and E7 played an important role in the pathogenesis of cervical carcinoma. The most common histological type is squamous cell carcinoma. Screening tests such as visual inspection with acetic acid (VIA), Pap smears and HPV DNA have an important role as modalities for early detection of malignancy. More specifically VIA and Pap smears are suitable for Indonesia which is a developing country, especially when implemented in peripheral areas.Keywords: oncogenesis; morphological changes; early detection; cervical carcinomaÂ Â Abstrak: Insidens dan mortalitas kanker serviks di negara berkembang relatif tinggi dibandingkan negara maju. Faktor risiko utama dari kanker serviks adalah infeksi human papilloma virus (HPV) risiko tinggi yaitu tipe 16 dan 18. HPV tipe risiko tinggi mengekspresikan onkoprotein E6 dan E7, yang berperan penting dalam patogenesis karsinoma serviks melalui inhibisi terhadap aktivitas produk-produk ekspresi kelompok gen yang berperan dalam menekan pertumbuhan tumor, seperti p53 dan pRB. Proses ini akan menyebabkan perubahan morfologik pada epitel skuamosa mulai dari lesi prakanker sampai kanker. Perkembangan kanker sel epitel skuamosa dapat dicegah melalui pemeriksaan skrining guna mendeteksi dini kanker serviks. Penelitian ini bertujuan untuk mengetahui onkogenesis, morfologi, dan modalitas deteksi dini karsinoma serviks. Jenis penelitian ialah literature review menggunakan tiga basis data yaitu ClinicalKey, PubMed, dan Google Scholar. Hasil penelitian mendapatkan bahwa penekanan p53 dan pRB oleh onkoprotein HPV risiko tinggi E6 dan E7 sangat berperan penting dalam patogenesis karsinoma serviks. Tipe histologik tersering ialah tipe karsinoma sel skuamosa. Pemeriksaan skrining seperti pemeriksaan inspeksi visual dengan asam asetat (IVA), Pap smear dan HPV DNA memiliki peran penting sebagai modalitas deteksi dini keganasan. Lebih khusus IVA dan Pap smear cocok untuk negara Indonesia yang merupakan negara berkembang, terutama bila diimplementasikan di daerah perifer.Kata kunci: onkogenesis; perubahan morfologik; deteksi dini; karsinoma serviks